A Conceptual Analysis of the Technology, Organisation, Environment, Readiness and Industry 4.0 Adoption in Malaysia Small and Medium Enterprises - ISMAIL, Siti Nurul Aziah; MOHAMED, Wan Norhayati; OMAR, Khatijah; MAT, Nik Hazimah Nik; SAPUTRA, Jumadil (Theoretical and Practical Research in Economic Fields, 2023)
Technology advancement is a primary element in differentiating Industry Revolution 4.0 (IR 4.0) from previous Industrial Revolutions. This revolution changes the nature of workforces, and the way people work. As a result of rapid technological advancement through Industry 4.0, SMEs are finding it more difficult to innovate and adopt. SMEs have difficulty adopting Industry 4.0; hence they tend to remain inactive. They can, however, reap greater benefits if they are more active and open to this new revolution. The current paper aims to examine the potential for reviewing to investigate, in the context of Malaysian SMEs and the adoption of Industry 4.0, whether the relationships between technology, organisations, environment, and Industry 4.0 adoption are mediated by readiness. Also, the paper analysed the various issues and concepts related to the study through various literatures. The study's results are expected to demonstrate that the relationships between technology, organisations, and environmental aspects are mediated by a readiness to adopt Industry 4.0. This finding will provide information to SMEs on which aspects for the company to improve to be ready and adopt Industry 4.0. It will also be useful to policymakers who create strategies and support systems to encourage the growth of Malaysian SMEs.